PERLINDUNGAN KONSUMEN TERHADAP PEMBULATAN KEATAS HARGA ARGOMETERTAKSI DI KOTA PEKANBARU - Sella M, Yuli Regita; Deliana, Evi; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Transportation is used to facilitate humans in carrying out daily activities. The role of transportation in the life of modern society is triggered by efforts to '' get closer '' distance, at first humans succeeded in creating a means of traveling (distance). The creation of this tool alone has given employment to a number of members of the community. With the increase in transportation means, the construction of facilities is also needed. Transportation is a means that is needed since ancient times in carrying out its activities that manifest in the form of transportation. In transportation services transactions, there is often a loss experienced by consumers in the transaction that is not in accordance with the listed taximeter prices.Research Objectives This study aims to determine consumer protection against rounding up the price of a taxi meter in the city of Pekanbaru. In order to know the efforts made by consumers for rounding up the price of the meter in the city of Pekanbaru. Location Research conducted at PT. RIAU TAXI at Jalan Harapan No.19 Pekanbaru, Bukit Raya District. This type of research is sociological researchIn collecting data, the types of data used in this study are primary data and secondary data, namely directly through respondents (field), Law No. 8 of 1999 concerning Consumer Protection, legal journals and books relating to research. This data analysis was conducted qualitatively and deductive conclusions were drawn.From the results of the research in this thesis, there are two main things that are concluded: First, the form of consumer protection against rounding up the price of a taxi meter in the city of Pekanbaru. And second, the efforts made by consumers towards rounding up the price of a taxi meter in the city of Pekanbaru.Keywords: Price of a meter - Business actors - Consumer Protection